1993
DOI: 10.1038/hdy.1993.3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis in the genus Aegilops. II. Interspecific hybrids between polyploid species sharing two common genomes

Abstract: Hybrids between polyploid Aegilops species sharing two common genomes were analysed at metaphase I by using a C-banding technique in order to establish genome relationships. In all cases it allowed discrimination between associations of chromosomes with similar morphology and C-banding belonging to the same genomes (homomorphic associations) and associations involving different chromosomes (heteromorphic associations). In the hybrids involving Ac. variabilis and Ae. kotschyi, (UUSS), it was also possible to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The existence of polyploid species such as Aegilops ventricosa (DDNN) and Aegilops juvenalis (DDMMUU) showed that the D genome could form intergenomic combinations with the N and M genomes. It was shown that in most cases the divergences between the shared genomes (U, D, or C) in different tetraploid species (Cuñado 1993a) and D, U, M, and N in hexaploid species (Cuñado 1993b) of Aegilops are, at present, substantial despite their common origin. Phylogenetic relationships among C, M, N, U, and common wheat genomes are shown in Figs.…”
Section: Discussionmentioning
confidence: 98%
“…The existence of polyploid species such as Aegilops ventricosa (DDNN) and Aegilops juvenalis (DDMMUU) showed that the D genome could form intergenomic combinations with the N and M genomes. It was shown that in most cases the divergences between the shared genomes (U, D, or C) in different tetraploid species (Cuñado 1993a) and D, U, M, and N in hexaploid species (Cuñado 1993b) of Aegilops are, at present, substantial despite their common origin. Phylogenetic relationships among C, M, N, U, and common wheat genomes are shown in Figs.…”
Section: Discussionmentioning
confidence: 98%